Exudative hyperresponsiveness of the airway microcirculation in seasonal allergic rhinitis - SVENSSON, C. (Clin Exp Allergy, 2006)
Background Mucosal exudation of plasma is a non‐injurious, physiological response of the airway microcirculation to different inflammatory processes. The exudative response is similar in the nose and bronchi and exudation occurs in both allergic asthma and rhinitis. The educative response is a specific end‐organ function of the mucosal microcirculation that may be altered in airway diseases. Objective This study examines the hypothesis of altered responsiveness of the superficial airway microcirculation to vascular permeability‐increasing challenges in sustained allergic inflammation. Methods Fourteen patients with birch‐pollen induced allergic rhinitis were studied for 7 weeks during a Swedish birch‐pollen season. Nasal symptoms (itching, sneezing. blockage, and discharge) were recorded and the occurrence of pollen was determined. The plasma exudation response was examined by topical histamine challenges at the end (May) and well out of (December) the season. Challenge and lavage were carried out concomitantly using a‘nasal pool’ ‐device. The unilateral nasal cavity was filled for consecutive 10 minute periods with saline and two concentrations of histamine (80μg/ mL and 400μg/mL). The lavage fluid levels of different‐sized plasma proteins (albumin‐66 000 D. fibrinogen‐340000 D, and α (2)‐macroglobulin‐725000D) were determined. Results The pollen season was mild resulting in only minor nasal symptoms. Histamine produced exudation of all plasma proteins across the microvascular epithelial barriers with particularly strong correlation between the levels of albumin and α (2)‐macroglobulin (r =0.98; P< 0.001). The exudative response to histamine was concentration‐dependent (P<0.05) and, furthermore, it was significantly greater late into the season compared with outside the pollen season (albumin: P < 0.05. tibrinogen: P<0.05. α (2)‐macroglobulin: P<0.01). Conclusion We conclude that histamine produced concentration‐dependent nasal airway exudation of bulk plasma in subjects with seasonal rhinitis and that this response is abnormally great during the pollen season. Whether angiogenesis or increased responsiveness of the mierovascular endothelium may explain this phenomenon now remains unknown. We suggest that a mierovascular exudative hyperresponsiveness may characterize allergic airway disease.